Art and Authority - Pop Art in the United States of America as model - Obeidat, Abdullah; Jawarneh, Sabreen (Dirasat: Human and Social Sciences, 2022)
The study discusses the subject of art and authority, and presents the experience of public art and the influence of authority in its various manifestations as a model., The study examined the concept from different points of view, In order to enrich the knowledge of the concept of authority. Then the study discussed the evolution of the relationship between power and art historically. The study aimed to identify the influence of authority strategies in guiding the philosophical thought of pop art and reveal the formal connotations that artists projected their works under the influence of authority. According to the stage the connection between art and authority developed. Among the most prominent manifestations of development is the decline in the influence of religious authority on Western consciousness in contrast to the growing influence of the power of money and politics, and the influence of the media and consumption. Among the most important results are: The different forms of power led to the enrichment of the expressionist scene of contemporary art in new expressive methods and tools at levels that touched the development of the collective consciousness of Western societies, especially the repercussions of the industrial and technological revolution that the authority sponsored, and it had the greatest impact on art and societies in the twentieth century, but it seemed invisible and wrapped in masks of freedom. Key words: art, authority, pop art.